2004
DOI: 10.1111/j.1365-313x.2004.02198.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of carotenoid biosynthesis in plants: evidence for a key role of hydroxymethylbutenyl diphosphate reductase in controlling the supply of plastidial isoprenoid precursors

Abstract: SummaryCarotenoids are isoprenoid pigments that function as photoprotectors, precursors of the hormone abscisic acid (ABA), colorants and nutraceuticals. A major problem for the metabolic engineering of high carotenoid levels in plants is the limited supply of their isoprenoid precursor geranylgeranyl diphosphate (GGPP), formed by condensation of isopentenyl diphosphate (IPP) and dimethylallyl diphosphate (DMAPP) units usually synthesized by the methylerythritol phosphate (MEP) pathway in plastids. Our earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
167
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(182 citation statements)
references
References 61 publications
12
167
0
3
Order By: Relevance
“…Fruit development in the tomato has been widely used as a system for these studies due to the observation that a significant increase in the supply of isoprenoid precursors is required to permit the massive accumulation of carotenoids that takes place during ripening. In this process, MEP-pathway key enzyme transcripts are accumulated; meanwhile, the transcript levels of the other MEP enzymes remain unchanged (Lois et al 2000, Rodriguez-Concepcion et al 2001, Botella-Pavia et al 2004. Despite the differences, P. falciparum intraerythrocytic development may be compared with tomato fruit ripening, since malaria parasites showed an increased biosynthesis of isoprenoids towards the end of schizogony (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruit development in the tomato has been widely used as a system for these studies due to the observation that a significant increase in the supply of isoprenoid precursors is required to permit the massive accumulation of carotenoids that takes place during ripening. In this process, MEP-pathway key enzyme transcripts are accumulated; meanwhile, the transcript levels of the other MEP enzymes remain unchanged (Lois et al 2000, Rodriguez-Concepcion et al 2001, Botella-Pavia et al 2004. Despite the differences, P. falciparum intraerythrocytic development may be compared with tomato fruit ripening, since malaria parasites showed an increased biosynthesis of isoprenoids towards the end of schizogony (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Maximal transcript levels in the schizont stage were concomitant with an increase in the ubiquinone biosynthesis and a reduction of the respective MEP pathway intermediate. Several studies showed that in tomato fruit ripening the accumulation of carotenoids only requires increased levels of DXS, DXR, and LytB transcripts (Lois et al 2000, RodriguezConcepcion et al 2001, Botella-Pavia et al 2004). Interestingly, we observed a positive correlation in P. falciparum between enhanced isoprenoid biosynthesis (ubiquinones) and accumulation of transcripts encoding all enzymes of the MEP pathway except for DXS.…”
mentioning
confidence: 99%
“…Thus we have identiWed two novel regulatory steps in the biosynthesis of TMTT in tomato. Kant et al (2004) have previously shown that DOXPS, the limiting step in plastidial IPP and DMAPP biosynthesis (Botella-Pavia et al 2004), was upregulated in tomato by spider mite-feeding ). This brings on the question why there are multiple steps in the biosynthesis of TMTT that are regulated.…”
Section: Leggps1 Is Not a Typical Ja-or Sa-responsive Genementioning
confidence: 98%
“…Exogenous application of GAs to the medium could partially rescue the dwarf phenotype of the pds3 mutant [30]. Other research indicated that levels of not only GAs but also other important compounds were decreased as a result of the metabolic disruption in the mutants of enzymes involved in the MEP pathway [21,[30][31][32][33][34]. However, no detailed analyses have been [30]).…”
Section: Introductionmentioning
confidence: 99%